Relationships Between Cognitive Impairment, Knowledge and Attitudes Among Drug Misusers Undergoing an Islamic Therapy in Malaysia. Issue 1 (2017) - Lua, Pei Lin; Embong, Nurul Haswani; Mohamad, Abdul Manam; Makhtar, Mokhairi; Jusoh, Julaily Aida; Abdullah, Azmi Hassan; Ramle
No abstract available